A perfect pony - Szymanski, Lois (New York : HarperFestival, 2005)
A PERFECT PONY It's the most exciting day of Niki's life! She's saved up enough money to buy her very own pony and today is the day of the pony auction. She could take home a magnificent pinto or a proud Thoroughbred, but she sets her heart on a beautiful white mare instead. When a little black horse with big sad eyes distracts Niki from the mare of her dreams, will she miss the chance to own the perfect pony?
O
700
O